International Ambidexterity: a competitive advantage of fashion industry firms in emerging markets - Krinke, Monica Facchini; Floriani, Dinora Eliete; Bueno, Giovana; Garrido, Ivan Lapuente (Revista de Negócios, 2021)
Firms from emerging markets (EMs) which are characterized by uncertainty and dynamism need to develop an ambidextrous approach in order to manage the dimensions of exploitation and exploration (E&E) and transform them into competitive advantages. However, there is not consensus on the ideal balance between exploitation and exploration within academia yet. The objective of this study aimed to understand the relationship between international commitment and international ambidexterity as a means of explaining competitiveness in fashion industry firms in EMs. We used a qualitative research was carried out through a multiple case study in three prominent companies in the Brazilian Fashion Industry. Our results showed the simultaneous international ambidexterity as a key element for building competitive advantage, driving the growth of firms from EMs and enabling them to survive in global markets. Our study seeks to provide insights into the importance of internationalization for the development of dynamic capabilities and consequently of increased international commitment through international ambidexterity.